2012
DOI: 10.1007/s10815-012-9759-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum anti-Mullerian hormone levels correlate with ovarian response in idiopathic hypogonadotropic hypogonadism

Abstract: Purpose The role of serum AMH levels in prediction of ovarian response in idiopathic hypogonadotropic hypogonadism (IHH) was evaluated. Material method(s) Twelve patients with IHH underwent controlled ovarian hyperstimulation (COH) for IVF were enrolled in this prospective study. Serum AMH levels were studied on the 2nd or 3rd day of an induced menstrual cycle by a preceding low-dose oral contraceptive pill treatment. A fixed dose (150-300 IU/day) of hMG was given in all COH cycles. Correlations between serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Previous studies on ovarian function and TM mainly focused on ovarian reserve and generally supported an impairment: AMH and AFC are consistently lower [4,[7], [8], [9], [10], [11]]. Our data is in agreement with these findings since both biomarkers resulted reduced in exposed women.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies on ovarian function and TM mainly focused on ovarian reserve and generally supported an impairment: AMH and AFC are consistently lower [4,[7], [8], [9], [10], [11]]. Our data is in agreement with these findings since both biomarkers resulted reduced in exposed women.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies also revealed that patients with TM have lower levels of anti-Mullerian hormone (AMH) and reduced antral follicular count (AFC), suggesting that the peripheral excess of iron may also be toxic locally to the gonads, harming the ovarian reserve [4,[7], [8], [9], [10], [11]]. In addition, iron excess, in particular non-transferrin-bound iron and its redox active form, may actually impact on oocyte quality.…”
Section: Introductionmentioning
confidence: 99%
“…Women with HH have abnormalities in the HPG axis and ovarian function but have age‐dependent dormant follicles in their ovaries . Theoretically, optimal physiological activation of ovarian follicles via gonadotropin administration can induce the development of single follicles and prevent multiple pregnancies and OHSS.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, women with HH show symptoms of hypoestrogenism, ovulation disorders and amenorrhea. However, according to the data of an ovarian function biomarker, anti‐Müllerian hormone, most women with HH have age‐dependent ovarian reserve . Therefore, optimal induction of gonadotropin secretion by pulsatile GnRH or continuous gonadotropin administration may improve folliculogenesis and ovulation, leading to improving pregnancy rates theoretically .…”
Section: Introductionmentioning
confidence: 99%
“…AMH may be useful to some extent. [ 4 ] Ovaries may or may not be seen on USG in these patients. Only after a patient is subjected to gonadotropin stimulation, we can estimate her pattern of response.…”
Section: Discussionmentioning
confidence: 99%